Gender and international migration in latin-american experience. From visibilization of the area to the selective presence - Herrera, Gioconda (Política y Sociedad, 2012)
In the last ten years the academic production on gender and migration has grown enormously, although many of this production signify, above all, the approach to the experience of women in migration processes. No longer can we speak of the invisibility of the issue as raised in the reviews carried up ten or fifteen years ago. This paper intends to develop three ideas about the presence of selective migration and gender studies based on the research on migration in Ecuador. The first idea is that this relationship between gender and migration is not new and that we should revisit old debates about gender and agrarian structure transformations that occurred in Latin America, mainly in the Andean region in the years 1970 and 1980 to understand the changes in the international migration, particularly on the experiences of migrant circuits where processes related internal and external migration. The second idea is to point out that a fundamental step observed in studies on gender and migration is turning a look of women’s experience with attempts to analyze the gendered character of migration processes and institutions: the labor market, migration policies, family reproductive strategies, among others. Finally, the third idea is to identify the contributions from gender studies to rethink the family, the family crime, transnational motherhood, fatherhood, crime, transnational childhoods. At this point, I think that international migration is a strategic body for analysis of family institution in global partnerships and that transnational perspective enables us to go beyond rigid interpretations of social change.